(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The use of modular education in the teaching of science is one of the main issues of the present day due to the expansion of our possibility of practical use of advanced communication-technologies with special attention to advanced forms of teaching in the educational process, the introduction of new pedagogical and information and communication technologies, the development of a distance learning system. Each discipline, including economic sciences, as a specialty discipline, also has its own characteristics of accounting. Only when we take into account the peculiarities of each subject will we choose an effective method of conducting classes, according to which it will be possible to ensure that the student, students, actively participate in the lesson.